Analyzing Shigella in Wuhan: Serotypes, Antimicrobial Resistance, and Public Health Implications - Deng S; Li C; Zhang H; Xie Y; Wang X; Luo W; Chen Z; Tang F (Infection and Drug Resistance)
Shiyong Deng,1,* Changzhen Li,1,* Hui Zhang,2,* Yuduan Xie,3,* Xiaomei Wang,1,* Wanjun Luo,4 Zhi Chen,5 Feng Tang1 1Department of Laboratory Medicine, Wuhan Children’s Hospital (Wuhan Maternal and Child Healthcare Hospital), Tongji Medical College, Huazhong University of Science & Technology, Wuhan, 430016, People’s Republic of China; 2Laboratory Department, Qiaokou Center for Disease Control and Prevention, Wuhan, 430030, People’s Republic of China; 3Department of Clinical Laboratory, Wangjing Hospital of China Academy of Chinese Medical Sciences, Beijing, 100102, People’s Republic of China; 4Hospital-Acquired Infection Control Department, Wuhan Children’s Hospital (Wuhan Maternal and Child Healthcare Hospital), Tongji Medical College, Huazhong University of Science & Technology, Wuhan, 430016, People’s Republic of China; 5Microbiological Laboratory, Wuhan Center for Disease Control and Prevention, Wuhan, 430024, People’s Republic of China*These authors contributed equally to this workCorrespondence: Feng Tang, Email tang33feng66@163.com Zhi Chen, Email 694867557@qq.comObjective: This study aims to delineate the epidemiological characteristics and antibiotic resistance of Shigella flexneri isolates from Wuhan, focusing on serotype distribution, resistance patterns, and genetic diversity.Methods: Our study analyzed 40Shigella flexneri isolates collected from 2011 to 2022 in Wuhan, assessing their serotype distribution and resistance to multiple antibiotics. We conducted resistance gene detection and genetic diversity analysis using polymerase chain reaction and pulsed-field gel electrophoresis (PFGE), respectively.Results: The study revealed significant clustering of S. flexneri in the Jianghan and Dongxihu districts, with serotype 2a predominating. Isolates exhibited high resistance to ampicillin, tetracycline, and trimethoprim-sulfamethoxazole, with an overall multidrug resistance (MDR) rate of 67.5%. Serotypes 1b and 2b were fully sensitive, contrasting with higher resistance in serotypes 2a and 4a to fluoroquinolones. Resistance mechanisms included blaOXA and blaTEM for ampicillin, blaCTX-M for cephalosporins, tetB for tetracycline, and dfrA1 and sul2 for trimethoprim-sulfamethoxazole. All 12 quinolone-resistant isolates exhibited mutations in gyrA (S83L, D87N, D87G), parC (S80I), and parE ( 458A), and novel mutations were identified in gyrA (H221Y, A221V, A221E, I222N), parC (D197A), and parE (G408D). Pulsed-field gel electrophoresis (PFGE) analysis highlighted extensive genetic diversity with dominant groups P1 and P4, and with notable regional and temporal distribution patterns. Distinct PFGE types exhibited unique antimicrobial resistance profiles, with P1 and P4 showing high rates of multidrug resistance, while P5 and P3 displayed lower resistance levels. A notable evolutionary adaptation was observed in a clone from 2016 (P4-1), which by 2017 (P4-2) had acquired aminoglycoside resistance.Conclusion: The study underscores the significant regional specificity and genetic diversity of S. flexneri in Wuhan, which poses challenges for treatment due to high antibiotic resistance and MDR prevalence. Findings stress the need for enhanced surveillance and tailored public health strategies to manage shigellosis effectively.Keywords: Shigella flexneri, epidemiology, resistance profile, multidrug resistance, pulsed-field gel electrophoresis